Grain-oriented electrical steel sheet and its manufacturing method

By adjusting nitriding gas exposure time and controlling elemental compositions, the method achieves reduced hysteresis loss and improved magnetic properties in grain-oriented electrical steel sheets.

JP2024546173AInactive Publication Date: 2024-12-17POHANG IRON & STEEL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024537603
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-01
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing grain-oriented electrical steel sheets struggle to maintain low hysteresis loss while reducing thickness, as precipitates flow away during secondary recrystallization, leading to uneven oxide layers and increased hysteresis loss, and the addition of elements like Sb, Sn, and Cr results in non-uniform coatings and magnetic property deviations.

Method used

Adjusting the exposure time of nitriding gas during primary recrystallization annealing to satisfy the formula △[N]/△t≧0.025, combined with specific elemental compositions and controlled oxidation power, to form a uniform metal oxide layer and minimize hysteresis loss.

Benefits of technology

The method significantly reduces hysteresis loss and overall core loss by ensuring uniform nitriding and oxidation, resulting in improved magnetic properties and reduced iron loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546173000001
    Figure 2024546173000001
  • Figure 2024546173000002
    Figure 2024546173000002
  • Figure 2024546173000003
    Figure 2024546173000003
Patent Text Reader

Abstract

The present invention provides a grain-oriented electrical steel sheet and a manufacturing method thereof that dramatically reduces the ratio of hysteresis loss in total iron loss by adjusting the exposure time to nitriding gas during primary recrystallization annealing. [Solution] A method for producing grain-oriented electrical steel sheet of the present invention includes the steps of hot rolling a slab containing, by weight, 2.5 to 4.0% Si, 0.03 to 0.09% C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (excluding 0%) S, 0.002 to 0.012% N, 0.01 to 0.05% Sb, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the balance being Fe and unavoidable impurities, to produce a hot-rolled sheet, cold rolling the hot-rolled sheet to produce a cold-rolled sheet, performing primary recrystallization annealing on the cold-rolled sheet, and performing secondary recrystallization annealing on the steel sheet after the primary recrystallization annealing has been completed. a step of measuring an amount of nitriding of the steel sheet after the primary recrystallization annealing; and a step of adjusting an exposure time to a nitriding gas during the primary recrystallization annealing in accordance with the measured amount of nitriding, wherein the amount of nitriding and the exposure time to the nitriding gas satisfy the following formula 1: [Formula 1] △[N] / △t≧0.025 (In formula 1, Δ[N] represents the amount of nitriding (wt %) of the steel sheet after the primary recrystallization annealing, and Δt represents the exposure time (min) to the nitriding gas.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a grain-oriented electrical steel sheet and a manufacturing method thereof, and more particularly to a grain-oriented electrical steel sheet in which the ratio of hysteresis loss in total iron loss is dramatically reduced by adjusting the exposure time to nitriding gas during primary recrystallization annealing, and a manufacturing method thereof. [Background technology]

[0002] Grain-oriented electrical steel sheets are used as iron core materials for stationary equipment such as transformers, electric motors, generators, and other electronic devices. The final product of grain-oriented electrical steel sheets has a texture in which the crystal grains are oriented in the 110

[0001] direction, and therefore has extremely excellent magnetic properties in the rolling direction, so it can be used as iron core materials for transformers, electric motors, generators, and other electronic devices. Low iron loss is required to reduce energy loss, and high magnetic flux density is required to reduce the size of power generation equipment. The iron loss of grain-oriented electrical steel sheets is divided into hysteresis loss and eddy current loss, and in order to reduce eddy current loss, it is necessary to make efforts such as increasing the specific resistivity and reducing the thickness of the product sheet. In order to reduce the thickness of the product sheet, it is difficult to roll grain-oriented electrical steel sheets, which are difficult to roll, into extremely thin sheets. In addition, the biggest difficulty and problem that must be overcome in making extremely thin products with very low iron loss characteristics is that it is difficult to make the concentration of the Goss orientation of the secondary recrystallization structure of grain-oriented electrical steel sheets very strong as the thickness becomes thinner. Hysteresis loss increases when the movement of the magnetic domain walls is hindered by fine precipitates and inclusions, but the base material of the final product must be kept very clean with very few components such as C, N, O, and S, and the stronger the Goss concentration, the greater the decrease in hysteresis loss.

[0003] This is because as the product thickness becomes thinner, the precipitates are washed away quickly from the surface during the secondary recrystallization annealing process, especially in the section where secondary recrystallization of the Goss orientation occurs, making it difficult to maintain a strong concentration of the Goss orientation. This is directly related to the magnetic properties of the product, and makes it difficult to ensure very low iron loss properties even when the thickness is made very thin. In addition, as the product becomes thinner, the ratio of the coating layer to the total product thickness increases. As the metal oxide layer (base coating, glass coating) on ​​the base material becomes thicker, the ratio of the coating layer to the product increases, which may worsen hysteresis loss.

[0004] As a method to overcome the precipitate washing out, a method has been proposed in which the N2 gas ratio is increased during the secondary recrystallization annealing process to prevent the precipitate washing out, but this has the problem of inducing surface defects such as nitrogen release holes on the surface of the product sheet. An economical manufacturing method using the simultaneous decarbonization-nitriding method has also been proposed. It has been clearly shown that when manufacturing decarburized plates using the simultaneous decarbonization-nitriding method, there is a difference between the grain size of the surface and the grain size of the center layer, and it has been proposed that this difference needs to be controlled within a certain range.

[0005] There has also been a proposal to dramatically improve magnetic properties by including segregation elements such as Sb, Sn, and P. Segregation elements have been used as auxiliary inhibitors to supplement the loss of precipitates when manufacturing ultra-thin products by adding more segregation elements, but adding too much makes ultra-thin rolling difficult, and adding too much of the segregation elements makes the oxide layer uneven and thin, which deteriorates the properties of the base coating, and has the side effect of causing further loss of precipitates, making it difficult to ensure stable magnetic properties. A method of adjusting the oxidation ability and nitriding treatment of the front end in the first recrystallization annealing process when manufacturing ultra-thin products has also been proposed. However, there is a problem in that the effect of precipitates being washed away is very sensitive when manufacturing ultra-thin products. Another method proposed is to add Cr to the slab and adjust the amount of nitriding gas input at the front and rear ends during the first recrystallization annealing process. However, this method maintains a uniform amount of nitrogen in the thickness direction of the steel sheet, but has the problem that AlN precipitates are distributed unevenly, resulting in deviations in magnetic properties. In addition, the addition of Cr deepens the oxide layer and thickens the base coating, which increases the proportion of the coating layer in the product, increasing the hysteresis loss of thin products.

[0006] The decarburization and nitriding reactions during the primary recrystallization annealing take place through the surface layer of the steel sheet. The speed and timing of decarburization and nitriding depend on the shape of the oxide layer formed on the surface layer. The depth and composition of the oxide layer formed during the primary recrystallization annealing process are sensitive to factors such as temperature, furnace atmosphere (oxidizing power), content of elements in the base steel, and surface shape. In particular, elements such as Sb, Sn, and Cr change the behavior of the oxide layer formation depending on the amount added, which ultimately affects the characteristics of the product, so it is necessary to derive the optimal conditions according to the product characteristics. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a grain-oriented electrical steel sheet and a manufacturing method thereof, specifically, a grain-oriented electrical steel sheet in which the ratio of hysteresis loss in total iron loss is dramatically reduced by adjusting the exposure time to nitriding gas during primary recrystallization annealing, and a manufacturing method thereof. [Means for solving the problem]

[0008] The method for producing grain-oriented electrical steel sheet of the present invention includes the steps of hot rolling a slab containing, by weight, 2.5 to 4.0% Si, 0.03 to 0.09% C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (excluding 0%) S, 0.002 to 0.012% N, 0.01 to 0.05% Sb, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the balance being Fe and other unavoidably mixed impurities, to produce a hot-rolled sheet, cold rolling the hot-rolled sheet to produce a cold-rolled sheet, performing primary recrystallization annealing on the cold-rolled sheet, and performing secondary recrystallization annealing on the steel sheet after the primary recrystallization annealing. The step of performing the primary recrystallization annealing includes a step of measuring the amount of nitriding of the steel sheet after the primary recrystallization annealing, and a step of adjusting the exposure time to the nitriding gas during the primary recrystallization annealing in accordance with the measured amount of nitriding, and the amount of nitriding and the exposure time to the nitriding gas satisfy the following formula 1. [Formula 1] △[N] / △t≧0.025 (In formula 1, △[N] represents the amount of nitriding (wt%) of the steel sheet after the first recrystallization annealing, and △t represents the exposure time (min) to the nitriding gas.)

[0009] The slab further contains at least one of Ti and V in an amount of 0.002 to 0.01% by weight, either alone or in total. The slab further contains 0.01 to 0.05 wt % Sb, 0.03 to 0.1 wt % Sn, and Cr, and satisfies the following formula 2. [Formula 2] [Sb]≦[Cr]≦[Sb]+2×[Sn] (In formula 2, [Sb], [Cr] and [Sn] represent the contents (weight%) of Sb, Cr and Sn in the slab, respectively.)

[0010] The first recrystallization annealing step is carried out in an atmosphere with an oxidation power (PH2O / PH2) of 0.5 to 0.8. The first recrystallization annealing step is carried out at a temperature of 800 to 900°C. After the step of primary recrystallization annealing, an oxide layer having an average thickness of 1.6 to 3.2 μm exists on the surface of the steel sheet. After the step of primary recrystallization annealing, the amount of nitriding of the steel sheet is 0.02 to 0.04 wt %.

[0011] The grain-oriented electrical steel sheet of the present invention comprises a base material which contains, by weight, 2.5 to 4.0% Si, 0.005% or less (excluding 0%) C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (excluding 0%), 0.005% or less (excluding 0%) N, 0.01 to 0.05%, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the remainder being Fe and other unavoidably mixed impurities, and a metal oxide layer located on the base material. The maximum (Max) emission intensity ratio [I(Ti) / I(Mg)] of the metal oxide layer is 0.05 or more.

[0012] The base metal further contains at least one of Ti and V, either alone or in a total amount of 0.002 to 0.01 wt %. The base material further contains 0.01 to 0.05 wt % Sb, 0.03 to 0.1 wt % Sn, and Cr, and satisfies the following formula 2. [Formula 2] [Sb]≦[Cr]≦[Sb]+2×[Sn] (In formula 2, [Sb], [Cr], and [Sn] represent the contents (by weight) of Sb, Cr, and Sn in the base material, respectively.) The whiteness of grain-oriented electrical steel sheet is 43 to 51. The metal oxide layer contains 0.003 wt % or more of Ti. The grain-oriented electrical steel sheet further includes an insulating coating layer located on the metal oxide layer, and a ratio of the total thickness of the metal oxide layer and the insulating coating layer to the total thickness of the grain-oriented electrical steel sheet is 0.03 or less. Effect of the Invention

[0013] The grain-oriented electrical steel sheet of the present invention can dramatically reduce the ratio of hysteresis loss in total iron loss by adjusting the exposure time to nitriding gas during primary recrystallization annealing, ultimately reducing total iron loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention. The terminology used herein is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. The term "comprising" as used in the specification means to embody certain features, regions, integers, steps, operations, elements and / or components and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements and / or components.

[0015] When we refer to an item as being "on" or "above" another item, it means that it is immediately on or above the other item, or there may be other items between them. In contrast, when we refer to an item as being "directly on" another item, there are no other items between them. Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person having ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the currently disclosed content, and are not interpreted in an ideal or very formal sense unless defined. Moreover, unless otherwise specified, % means % by weight, and 1 ppm is 0.0001% by weight. In one embodiment of the present invention, the additional element is included to substitute the remaining iron (Fe) with the additional amount of the additional element.

[0016] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail so as to be readily understood by those skilled in the art to which the present invention pertains. However, the present invention may be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. The method for producing grain-oriented electrical steel sheet of the present invention includes the steps of hot rolling a slab containing, by weight, 2.5 to 4.0% Si, 0.03 to 0.09% C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (excluding 0%) S, 0.002 to 0.012% N, 0.01 to 0.05% Sb, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the balance being Fe and unavoidable impurities, to produce a hot-rolled sheet, cold rolling the hot-rolled sheet to produce a cold-rolled sheet, performing primary recrystallization annealing on the cold-rolled sheet, and performing secondary recrystallization annealing on the steel sheet after the primary recrystallization annealing.

[0017] Each step will be explained in detail below. First, a slab is hot rolled to produce a hot-rolled sheet. The slab alloy ingredients are described below. The slab contains, by weight, Si: 2.5 to 4.0%, C: 0.03 to 0.09%, Al: 0.015 to 0.040%, Mn: 0.04 to 0.15%, S: 0.01% or less (excluding 0%), N: 0.002 to 0.012%, Sb: 0.01 to 0.05%, Sn: 0.03 to 0.1% and Cr: 0.05 to 0.2%, with the remainder being Fe and unavoidable impurities.

[0018] Si: 2.50 to 4.00% by weight Silicon (Si) plays a role in increasing the resistivity of grain-oriented electrical steel sheet material and reducing core loss, i.e., iron loss. If the Si content is too low, the resistivity may decrease and the iron loss may deteriorate. If the Si content is too high, the brittleness of the steel increases, the toughness decreases, the incidence of plate breakage during the rolling process increases, the weldability deteriorates, a load is placed on the cold rolling operation, and the plate temperature required for pass aging during cold rolling is not reached, which may cause unstable secondary recrystallization formation. Therefore, the Si content may be 2.5 to 4.0 wt. %. More specifically, it may be 3.0 to 3.5 wt. %.

[0019] C: 0.030 to 0.090% by weight Carbon (C) is an element that induces the formation of austenite phase. As the C content increases, the ferrite-austenite phase transformation during the hot rolling process is activated, the long drawn hot strip structure formed during the hot rolling process is increased, and the ferrite grain growth during the hot rolled sheet annealing process is suppressed. In addition, as the C content increases, the drawn hot strip structure, which has higher strength than the ferrite structure, increases, and the initial grains of the hot rolled sheet annealing structure at the start of cold rolling are refined, improving the texture after cold rolling, and in particular increasing the Goss fraction. This is thought to be because the residual C present in the steel sheet after hot rolled sheet annealing increases the pass aging effect during cold rolling, increasing the Goss fraction in the primary recrystallized grains. Therefore, the higher the C content, the better, but the longer the decarburization annealing time during the subsequent decarburization nitriding annealing, damaging productivity, and if decarburization at the beginning of heating is insufficient, the primary recrystallized grains become non-uniform, making the secondary recrystallization unstable. Also, since the magnetic properties may be deteriorated due to the magnetic aging phenomenon, the C content may be limited to the range of 0.03 to 0.09 wt %. More specifically, C may be contained in the range of 0.050 to 0.070 wt%. As described above, carbon is removed by decarburization during the primary recrystallization annealing, and the base material of the finally manufactured grain-oriented electrical steel sheet may contain 0.005 wt% or less of C. Even more specifically, C may be contained in the base material of the finally manufactured grain-oriented electrical steel sheet may contain 0.003 wt% or less of C.

[0020] Al: 0.015 to 0.040% by weight Aluminum (Al) combines with N to precipitate as AlN, and forms fine precipitates of (Al,Si,Mn)N and nitrides in the form of AlN during annealing for decarburization and nitridation, which plays a strong role in suppressing grain growth. A certain amount of dissolved Al is necessary. If the content is too low, the number and volume fraction of precipitates formed are low, so the effect of suppressing grain growth may be insufficient. If too much Al is included, the precipitates grow coarsely, reducing the effect of suppressing grain growth. Therefore, Al may be included in an amount of 0.015 to 0.040 wt. %. More specifically, it may be included in an amount of 0.0200 to 0.0380 wt. %.

[0021] Mn: 0.040 to 0.150% by weight Manganese (Mn) has the effect of increasing resistivity and reducing iron loss, just like Si, and is an important element for suppressing the growth of primary recrystallization grains and inducing secondary recrystallization by reacting with nitrogen introduced by nitriding together with Si to form (Al, Si, Mn)N precipitates. Mn also forms surfide precipitates together with Cu to improve the uniformity of primary recrystallization grains and to play a role as an auxiliary inhibitor for the formation of secondary recrystallization. However, if Mn is included too much, the slab reheating temperature must be increased to adjust the (Cu, Mn)S fine precipitates, and the primary recrystallization grains become extremely fine, and the temperature of the primary recrystallization annealing must be increased beyond the range, which causes non-uniformity of the grains, so the upper limit may be limited to 0.15 wt%. In addition, when Mn is added in excess, a large amount of (Fe, Mn) and Mn oxides other than Fe2SiO4 are formed on the surface of the steel sheet, which impedes the formation of a base coating during secondary recrystallization annealing and reduces surface quality, and induces non-uniformity in the phase transformation between ferrite and austenite during the primary recrystallization annealing process, which makes the size of the primary recrystallized grains non-uniform, resulting in unstable secondary recrystallization.More specifically, Mn may be included in an amount of 0.050 to 0.100 wt%.

[0022] N: 0.0020 to 0.0120% by weight Nitrogen (N) is an element that reacts with Al and the like to refine the crystal grains. When these elements are appropriately distributed, as described above, it is useful for properly refining the structure after cold rolling and ensuring an appropriate primary recrystallization grain size. However, if the content is excessive, the primary recrystallization grains become excessively fine, and as a result, the driving force that causes grain growth during secondary recrystallization due to the fine crystal grains becomes large, which is undesirable because it may cause crystal grains to grow in an undesirable orientation. And if too much N is added, the primary recrystallization grains become excessively fine, and as a result, the fine crystal grains may form secondary recrystallization in an undesirable orientation, which may deteriorate the magnetic properties. Therefore, the N content is set to 0.0120 wt% or less. On the other hand, if the N content is too low, the primary recrystallization inhibition effect is too weak and a stable grain growth inhibition effect may not be obtained. Therefore, the slab may contain 0.0020 to 0.0120 wt% N. More specifically, it may contain 0.0025 to 0.0100 wt% N. Since N is partially removed during the secondary recrystallization annealing process, the base material of the finally manufactured grain-oriented electrical steel sheet may contain 0.005 wt% or less N. Even more specifically, the base material of the finally manufactured grain-oriented electrical steel sheet may contain 0.003 wt% or less N.

[0023] S: 0.0100% by weight or less, Sulfur (S) is an element that has a high solid solution temperature and is highly segregated during hot rolling, and it is preferable to avoid its inclusion as much as possible, but it is an unavoidable impurity that is included during steelmaking. In addition, S forms (Mn, Cu)S and affects the uniformity of primary recrystallized grains, so the S content may be limited to 0.0100% by weight or less. More specifically, it may be contained in the range of 0.0010 to 0.0080% by weight.

[0024] Sb: 0.01 to 0.05% by weight Antimony (Sb) increases the number of crystal grains with Goss orientation generated during the cold rolling process, and improves the fraction of crystal grains with Goss orientation in the primary recrystallization texture. It also segregates in the primary recrystallization grain system and increases the secondary recrystallization start temperature of crystal grains with Goss texture during high-temperature annealing for secondary recrystallization, thereby obtaining a secondary recrystallization fine texture with excellent integration and increasing magnetic flux density. If the Sb content is too low, it is difficult to achieve its effect. If the Sb content is too high, the size of the primary recrystallization grains becomes too small, the secondary recrystallization start temperature becomes low, and the magnetic properties are deteriorated or the suppression force against grain growth becomes too large, so that secondary recrystallization may not be formed. Therefore, Sb may be contained in an amount of 0.01 to 0.05 wt %. More specifically, Sb may be contained in an amount of 0.020 to 0.045 wt %.

[0025] Sn: 0.03 to 0.10% by weight Tin (Sn) is a grain segregation element that prevents the movement of grains, and is therefore known as a grain growth inhibitor. In addition, by increasing the fraction of grains with Goss orientation in the primary recrystallization texture, the number of Goss orientation nuclei that grow into the secondary recrystallization texture increases. In addition, the more Sn is added, the smaller the size of the secondary recrystallization microstructure becomes, and the smaller the grain size becomes, the smaller the eddy current loss becomes, so the iron loss of the final product decreases. Meanwhile, Sn plays an important role in inhibiting grain growth through its segregation in the grains. This not only improves the inhibiting effect of inhibiting the driving force of grain growth in the refined primary recrystallization microstructure, but also prevents the phenomenon in which particles that cause grain growth inhibition effects, such as (Al, Si, Mn)N and AlN, become coarse during the high-temperature annealing process for the formation of the secondary recrystallization texture, thereby reducing the grain growth inhibition effect. If the Sn content is too low, the effect of addition may be insufficient. If the Sn content is too high, the grain growth inhibition force increases excessively, and the grain size of the primary recrystallized microstructure must be reduced to relatively increase the driving force for grain growth, so decarburization annealing must be performed at a low temperature, and as a result, a good surface cannot be secured because an appropriate oxide layer cannot be controlled. In addition, in terms of mechanical properties, the brittleness increases due to excessive segregation of grain boundary segregation elements, which may cause plate breakage during the manufacturing process. Therefore, Sn may be contained at 0.03 to 0.10 wt%. More specifically, Sn may be contained at 0.030 to 0.090 wt%.

[0026] Cr: 0.05 to 0.20% by weight Adding chromium (Cr) within a certain range as an element that promotes oxide formation suppresses the formation of a dense oxide layer on the surface and helps to form a fine oxide layer in the depth direction. Adding an appropriate range of Cr content together with the addition of Sb and Sn increases the formation of Fe2SiO4 on the surface of the oxide layer, helping to form the oxide layer in the depth direction. In addition, the addition of Cr makes it easier to form a primary recrystallization with excellent uniformity. In other words, Cr is an element that overcomes the phenomenon that the primary recrystallization grains become non-uniform due to the delay in decarburization and nitriding caused by increasing the Sb and Sn contents, thereby forming primary recrystallization grains with excellent uniformity and improving magnetic properties. When the Cr content is added within the range proposed according to the Sb and Sn contents, the inner oxide layer is formed deeper and the nitriding and decarburization speed is increased, so that the effect of adding Sb and Sn in the simultaneous decarburization and nitriding process can be enhanced. Cr may be included in an amount of 0.05 to 0.20 wt %. More specifically, it may be included in an amount of 0.10 to 0.15 wt %.

[0027] The slab may satisfy Equation 2 below. [Formula 2] [Sb]≦[Cr]≦[Sb]+2×[Sn] (In formula 2, [Sb], [Cr] and [Sn] represent the contents (weight%) of Sb, Cr and Sn in the slab, respectively.) Adding chromium (Cr) within a certain range as an element that promotes oxide formation suppresses the formation of a dense oxide layer on the surface and helps to form a fine oxide layer in the depth direction. Adding an appropriate range of Cr content together with the addition of Sb and Sn increases the formation of Fe2SiO4 on the surface of the oxide layer, helping to form the oxide layer in the depth direction.

[0028] Also, the addition of Cr makes it easier to form primary recrystallization with excellent uniformity. In other words, Cr is an element that overcomes the phenomenon of primary recrystallization grains becoming non-uniform due to delayed decarburization and nitriding caused by increasing the Sb and Sn contents, thereby forming primary recrystallized grains with excellent uniformity and improving magnetic properties. When the Cr content is added within the range suggested above according to the Sb and Sn contents, the internal oxide layer is formed deeper and the nitriding and decarburization speeds are increased, so that the effect of adding Sb and Sn in the simultaneous decarburization and nitriding process can be enhanced. If the Cr content does not reach the lower limit of formula 2, the effect is weak, whereas if it exceeds the upper limit of formula 2, an excessive oxide layer is formed, reducing the effect.

[0029] The slab may further contain at least one of Ti and V, either alone or in a total amount of 0.002 to 0.010 wt %. When Ti and V are contained alone, each may be contained at 0.002 to 0.010 wt %, and when Ti and V are contained simultaneously, the amount of Ti+V may be 0.002 to 0.010 wt %. More specifically, the slab may further contain at least one of Ti and V, either alone or in a total amount of 0.0030 to 0.0070 wt %.

[0030] Ti: 0.002 to 0.010% by weight Titanium (Ti) is a strong nitride forming element, which becomes TiN in the step before hot rolling to reduce the N content and suppresses grain growth by finely precipitating. When added within the appropriate range, it has the effect of suppressing grain growth by forming TiN precipitates, and the effect of reducing the deviation of grain size within the coil by reducing fine AlN precipitates.

[0031] V: 0.002 to 0.01% by weight Vanadium (V) is an element that forms carbides and nitrides, and it suppresses grain growth by forming fine precipitates. When added within an appropriate range, it has the effect of suppressing grain growth by forming fine precipitates, thereby reducing the grain size deviation in the coil.

[0032] The slab may further comprise P: 0.010 to 0.050 wt %. P: 0.010 to 0.050% by weight Phosphorus (P) is an element that has a similar effect to Sn and Sb, and it can segregate in the grain system, hinder the movement of the grain system, and at the same time, it can play a supplementary role in suppressing grain growth. In terms of the microstructure, it has a {110} <001> It has the effect of improving the texture. If the content of P is too low, the effect of adding it is not obtained, and if it is added too much, it may increase brittleness and significantly deteriorate rollability. More specifically, P may be contained in an amount of 0.015 to 0.045 wt%.

[0033] Impurity elements In addition to the above elements, impurities such as Zr, Cu, Ni, and Mo are inevitably mixed in. Since Zr, Cu, Ni, and Mo are strong carbide-forming elements, it is preferable to avoid adding them as much as possible, and each of them should be contained at 0.01% by weight or less. The remainder other than the above elements is iron (Fe). The present invention does not exclude the addition of elements other than the above alloy components, and various elements may be included within a range that does not harm the technical idea of ​​the present invention. When an additional element is further included, it is included to replace the remaining Fe.

[0034] Before the step of producing the hot-rolled sheet, the method may further include a step of heating the slab at 1230°C or less. This step allows the precipitates to be partially dissolved. In addition, the columnar grains of the slab are prevented from growing coarsely, and cracks in the width direction of the sheet are prevented from occurring in the subsequent hot rolling process, improving the yield. If the slab heating temperature is too high, the surface of the slab may melt, which may shorten the life of the furnace, such as requiring repairs. More specifically, the slab may be heated at 1130 to 1200°C. It is also possible to hot roll the continuously cast slab as it is without heating the slab. In the step of producing a hot-rolled sheet, a hot-rolled sheet having a thickness of 1.8 to 2.3 mm can be produced by hot rolling. The method may further include a step of annealing the hot-rolled sheet after manufacturing the hot-rolled sheet. The step of annealing the hot-rolled sheet may be performed by a process of heating the hot-rolled sheet to a temperature of 950 to 1,100°C, soaking the hot-rolled sheet to a temperature of 850 to 1,000°C, and then cooling the hot-rolled sheet.

[0035] Next, the hot-rolled sheet is cold-rolled to produce a cold-rolled sheet. Cold rolling can be performed through one strong cold rolling pass or multiple passes. During rolling, warm rolling can be performed at least once at a temperature of 200 to 300°C to give a pass aging effect, and the final thickness can be manufactured to 0.14 to 0.25 mm. The cold-rolled sheet undergoes decarburization and recrystallization of the deformed structure during the first recrystallization annealing process, and nitriding treatment using nitriding gas.

[0036] Next, the cold-rolled sheet is subjected to primary recrystallization annealing. The present invention includes a step of measuring the amount of nitriding of the steel sheet in the step of performing the primary recrystallization annealing, and adjusting the exposure time to the nitriding gas during the primary recrystallization annealing based on the measurement result. The amount of nitriding and the exposure time of the nitriding gas can be adjusted to satisfy the following formula 1. [Formula 1] △[N] / △t≧0.025 (In formula 1, △[N] represents the amount of nitriding (wt%) of the steel sheet after the first recrystallization annealing, and △t represents the exposure time (min) to the nitriding gas.)

[0037] In the present invention, since a process of adjusting the exposure time of the nitriding gas is performed after the measurement of the amount of nitriding, a delay may occur between the steel sheet for which the amount of nitriding is measured and the steel sheet for which the exposure time of the nitriding gas is adjusted. However, since the primary recrystallization annealing is performed continuously in the present invention, the delay may not be substantial and the relationship of Equation 1 may be satisfied within the entire coil.

[0038] The amount of nitriding means the difference between the N content in the steel sheet after the first recrystallization annealing and the N content in the steel sheet before the first recrystallization annealing. This is measured by a nitrogen analyzer, and the result can be reflected in adjusting the exposure time of the nitriding gas. There is no limitation on the method of measuring the amount of nitriding in real time, and since this is widely known, a detailed description will be omitted. The amount of nitriding of the steel sheet may be 0.02 to 0.04% by weight. If the amount of nitriding is too small, that is, if the value on the left side of Equation 3 is too large, the ability to inhibit the growth of internal crystal grains may be insufficient. If the amount of nitriding is too large, a large number of defects such as nitrogen release holes may occur, and a large number of fine secondary recrystallizations of 5 mm or less may be formed, which may deteriorate the magnetic properties.

[0039] The nitriding gas can be any gas that can cause nitrogen to penetrate the steel sheet. Specific examples include ammonia and nitrogen. Nitriding can be performed through heat treatment in an ammonia atmosphere, and through laser or plasma treatment in a nitrogen atmosphere. The exposure time of the nitriding gas can be adjusted by providing a shielding film in the annealing furnace to prevent the movement of the atmospheric gas in the moving direction of the steel sheet, and by introducing gas into the space separated by the shielding film so that the atmospheric gas can be adjusted to be different. In addition, the exposure time of the nitriding gas can be adjusted in various other ways. The exposure time to the nitriding gas means the time during which the steel sheet is exposed to an atmosphere containing 1 to 10% by volume of the nitriding gas. Outside the exposure time to the nitriding gas, the steel sheet is subjected to primary recrystallization annealing in an atmosphere containing less than 1.0% by volume of the nitriding gas.

[0040] The amount of nitriding of a steel sheet is proportional to the exposure time of the nitriding gas, but there are various other variables. For example, the temperature of the steel sheet, the content of atmospheric gases other than the nitriding gas, etc. Even if it is attempted to control these variables as much as possible, it is practically impossible to control them uniformly within the entire coil, and even if the exposure time of the nitriding gas is the same, there may be deviations in the amount of nitriding. Specifically, the exposure time of the nitriding gas may be 30 seconds to 5 minutes. If the amount of nitriding is too small compared to the exposure time of the nitriding gas, that is, if the value of formula 1 is too small, the precipitates are not formed uniformly and the metal oxide layer may be formed non-uniformly during the secondary recrystallization annealing process. This may cause surface defects and unstable magnetic properties. More specifically, the value of formula 1 may be 0.025 to 0.05.

[0041] The first recrystallization annealing step is performed in an atmosphere with an oxidation potential (PH2O / PH2) of 0.5 to 0.8, which allows the carbon in the steel sheet to be discharged to the outside. The above-mentioned oxidation potential range can be adjusted throughout the first recrystallization annealing step or partially. Through this, the carbon in the steel sheet can be reduced to 0.005 wt% or less. The step of primary recrystallization annealing may be performed at a temperature of 800 to 900° C. If the temperature is too low, the primary recrystallization may not occur or the nitriding may not proceed smoothly. If the temperature is too high, the primary recrystallization may grow too large, which may cause poor magnetic properties.

[0042] After the step of primary recrystallization annealing, an oxide layer with an average thickness of 1.6 to 3.2 μm may be present on the surface of the steel sheet. The oxide layer is present near the surface of the steel sheet due to decarburization during the primary recrystallization annealing. The oxide layer refers to the part from the surface of the steel sheet to the part where the oxygen content changes rapidly when the oxygen content is measured. If the oxide layer is too thin, the magnetic non-uniformity increases. If the oxide layer is too thick, the metal oxide layer is formed thick, which reduces the thickness of the base material relatively, and the magnetic properties may be deteriorated.

[0043] Next, the cold-rolled sheet that has completed the primary recrystallization annealing is subjected to secondary recrystallization annealing. The main purpose of secondary recrystallization annealing is to obtain {110} <001> The purpose of the secondary recrystallization annealing is to form a texture, to give insulation properties by forming a metal oxide layer through the reaction between the oxide layer formed during decarburization and MgO in the annealing separator, and to remove impurities that impair magnetic properties. The method of secondary recrystallization annealing is to maintain a mixture of nitrogen and hydrogen gas in the heating section before secondary recrystallization occurs to protect the nitride of the grain growth inhibitor so that secondary recrystallization develops well, and after secondary recrystallization is completed, to maintain a 100% hydrogen atmosphere for a long time to remove impurities. During the secondary recrystallization annealing process, as the nitride precipitates are decomposed, nitrogen is removed by passing through the metal oxide layer, but it may diffuse into the metal oxide layer and react with Ti to form TiN in some cases.

[0044] In the secondary recrystallization annealing process, the surface oxide layer formed in the primary recrystallization annealing process reacts with the annealing separator to form a metal oxide layer. The metal oxide layer is different in composition from the base material. For example, when MgO is used as the annealing separator, it contains forsterite. In the present invention, the annealing separator further contains a Ti compound in addition to MgO. More specifically, the annealing separator is a solid content and contains 90 to 99 wt % MgO and 1 to 10 wt % Ti compound. The method may further include forming an insulating coating layer after the second recrystallization annealing. A method for forming an insulating coating layer is well known, and therefore a detailed description thereof will be omitted.

[0045] In the present invention, the thickness of the metal oxide layer after the secondary recrystallization can be formed thin by adjusting the nitrogen content sufficiently high relative to the exposure time of the nitriding gas atmosphere, and an additional process of removing the metal oxide layer may not be included. Specifically, the ratio of the total thickness of the metal oxide layer and the insulating coating layer to the thickness of the entire grain-oriented electrical steel sheet including the metal oxide layer and the insulating coating layer may be 0.03 or less. More specifically, it may be 0.001 to 0.03.

[0046] The grain-oriented electrical steel sheet of the present invention comprises a base material which contains, by weight, 2.5 to 4.0% Si, 0.005% or less (excluding 0%) C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (excluding 0%), 0.005% or less (excluding 0%) N, 0.01 to 0.05%, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the remainder being Fe and unavoidable impurities, and a metal oxide layer located on the base material. The steel composition of the base material of grain-oriented electrical steel sheet has been described in relation to the steel composition of the slab, and therefore a duplicated description will be omitted. As described above, since decarburization and nitriding are performed during the manufacturing process of grain-oriented electrical steel sheet, the C and N contents in the steel composition of the slab and the steel composition of the base material may differ, and the remaining elements may not vary substantially.

[0047] The maximum (Max) emission intensity ratio [I(Ti) / I(Mg)] of the metal oxide layer of the present invention is 0.05 or more. The maximum emission intensity can be measured from the max intensity ratio of Ti and Mg components through elemental analysis of the metal oxide layer in the thickness direction by glow discharge surface analysis. In the present invention, by controlling the nitrogen content to a sufficiently high level relative to the exposure time of the nitriding gas atmosphere, local nitriding concentration is suppressed in the oxide layer and the lower part of the oxide layer, sufficient nitride precipitates are formed in the depth direction, and the metal oxide layer formed during the secondary recrystallization annealing is dense and uniform, so that the maximum emission intensity ratio can be high. A high maximum emission intensity ratio means that the metal oxide layer is firmly formed, which is advantageous for applying uniform tension and suppresses the loss of nitrogen before the formation of secondary recrystallization, which ultimately leads to improved magnetic properties.

[0048] The whiteness of the grain-oriented electrical steel sheet may be 43 to 51. The whiteness can be measured when there is no insulating coating layer or when it is removed and only the metal oxide layer is present. The whiteness can be measured by measuring both sides of the coating more than 10 times using a reflectance measurement method with a spectrophotometer and taking the average value. If the whiteness is too high, the metal oxide layer is formed unevenly, causing surface defects and large magnetic deviation. If the whiteness is too low, the thickness ratio of the metal oxide layer becomes too high, and magnetic properties deteriorate.

[0049] The metal oxide layer may contain 0.003 wt% or more of Ti. The Ti in the metal oxide layer may originate from a Ti compound component in the annealing separator, or may be present as a result of diffusion of Ti components in the steel sheet. If there is a small amount of Ti in the metal oxide layer, the metal oxide layer may be formed thin and non-uniform, and a coating defect problem may occur due to the formation of Fe oxide. More specifically, the metal oxide layer may contain 0.003 to 0.02 wt% of Ti. More specifically, the metal oxide layer may contain 0.005 to 0.02 wt% of Ti.

[0050] The thickness of the grain-oriented electrical steel sheet of the present invention may be 0.23 mm or less. More specifically, it may be 0.20 mm or less. Here, the thickness of the grain-oriented electrical steel sheet means the total thickness of the base material, the metal oxide layer, and the insulating coating layer. The grain-oriented electrical steel sheet according to the embodiment of the present invention has excellent core loss and magnetic flux density. Specifically, the core loss (W17 / 50) may be 0.8 W / kg or less, and the ratio of hysteresis loss in the total core loss may be 40% or less. In addition, the magnetic flux density (B8) induced in the grain-oriented electrical steel sheet under a magnetic field of 800 A / m may be 1.91 T or more. More specifically, it may be 1.91 to 1.97 T.

[0051] . Hereinafter, preferred examples and comparative examples of the present invention will be described. However, the following examples are merely preferred examples of the present invention, and the present invention is not limited to the following examples.

[0052] Working Example Slabs A to H, which have the composition shown in Table 1, were made by vacuum melting steel material consisting of the remainder Fe and other unavoidable impurities, forming ingots, heating them at 1150°C for 210 minutes, and then hot rolling them to produce hot-rolled sheets with a thickness of 2.3 mm or 2.0 mm. After pickling, they were subjected to one strong cold rolling at a reduction rate of 90% to a thickness of 0.23 mm or 0.20 mm. The cold-rolled sheet was subjected to a simultaneous decarbonitriding annealing heat treatment by maintaining it at a temperature of 850°C for 180 seconds in a moist 50v% hydrogen and 50v% nitrogen and ammonia mixed gas atmosphere so that the carbon content was 30ppm or less and the total nitrogen content was 200ppm or more. At this time, the ammonia gas volume fraction was adjusted to 1 to 10 volume %, the oxidizing power (PH2O / PH2) was adjusted to within the range of 0.5 to 0.8, and the amount of nitriding and the ammonia exposure time after nitriding were adjusted to satisfy the conditions shown in Table 2. The steel sheet was coated with an annealing separator containing 95% by weight of MgO and 25% by weight of TiO as solid contents, and then coiled for secondary recrystallization annealing. The secondary recrystallization annealing was performed in a mixed atmosphere of 25% by volume of nitrogen and 75% by volume of hydrogen up to 1200°C. After reaching 1200°C, the atmosphere was maintained at 100% by volume of hydrogen for 10 hours or more, and then the steel sheet was cooled in the furnace.

[0053] Thereafter, an insulating coating layer-forming composition containing a mixed liquid of metal phosphate and colloidal silica was applied, and heat-treated to form an insulating coating layer. The whiteness, maximum luminous intensity ratio [I(Ti) / I(Mg)], and hysteresis loss ratio measured under each condition are summarized in the following Table 2. The measurement methods are as follows. Whiteness: Measured using a spectrophotometer with reflectance measurement, measuring both sides of the coating 10 times or more and taking the average value. Maximum emission intensity ratio [I(Ti) / I(Mg)]: The ratio was measured from the max intensity of Ti and Mg components through elemental analysis of the metal oxide layer in the thickness direction using glow discharge surface analysis. Hysteresis loss ratio: The iron loss and hysteresis loss were measured for the test pieces manufactured under each condition, and the ratio of the hysteresis loss to the total iron loss was calculated.

[0054] [Table 1]

[0055] [Table 2]

[0056] As can be seen in Table 2, the inventive material, in which the exposure time to the nitriding gas was appropriately adjusted according to the amount of nitriding, had a large maximum luminescence intensity ratio [I(Ti) / I(Mg)], excellent magnetic properties, a particularly small hysteresis loss ratio, and small overall iron loss. In contrast, it can be seen that the comparative materials 1 to 4, in which the exposure time to the nitriding gas was not appropriately adjusted, have a small maximum luminescence intensity ratio [I(Ti) / I(Mg)] and are inferior in magnetism. It can be seen that, even though the exposure time to the nitriding gas was appropriately adjusted, the comparative materials 5 to 9, in which the Sb, Sn, and Cr contents were not appropriately adjusted, had inferior magnetic properties.

[0057] The present invention is not limited to the above-mentioned embodiments, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains should understand that the present invention can be embodied in other specific forms without changing the technical concept or essential features of the present invention. Therefore, the above-described embodiments should be understood to be illustrative in all respects and not restrictive.

Claims

1. hot rolling the slab containing, by weight percent, 2.5 to 4.0% Si, 0.03 to 0.09% C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less S (except 0%), 0.002 to 0.012% N, 0.01 to 0.05% Sb, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the balance being Fe and unavoidable impurities, to produce a hot rolled sheet; cold rolling the hot rolled sheet to produce a cold rolled sheet; A step of subjecting the cold-rolled sheet to a primary recrystallization annealing; and subjecting the steel sheet having undergone the first recrystallization annealing to a second recrystallization annealing. The step of performing the first recrystallization annealing includes: Measuring the amount of nitriding of the steel sheet after the primary recrystallization annealing; and adjusting the exposure time of the nitriding gas during the primary recrystallization annealing in accordance with the measured amount of nitriding. a nitriding amount and an exposure time of the nitriding gas satisfying the following formula 1: [Formula 1] △[N] / △t≧0.025 (In formula 1, Δ[N] represents the amount of nitriding (wt%) of the steel sheet after the primary recrystallization annealing, and Δt represents the exposure time (min) to the nitriding gas.)

2. 2. The method of claim 1, wherein the slab further contains at least one of Ti and V, either alone or in a total amount of 0.002 to 0.01 wt %.

3. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein the slab satisfies the following formula 2: [Formula 2] [Sb]≦[Cr]≦[Sb]+2×[Sn] (In formula 2, [Sb], [Cr] and [Sn] represent the contents (wt%) of Sb, Cr and Sn in the slab, respectively.)

4. The step of performing the first recrystallization annealing is carried out by adjusting the oxidation ability (PH 2 O / P 2 2. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein the temperature is 0.5 to 0.

8.

5. The method of claim 1, wherein the first recrystallization annealing is performed at a temperature of 800 to 900°C.

6. 2. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein an oxide layer having an average thickness of 1.6 to 3.2 μm exists on the surface of the steel sheet after the step of the primary recrystallization annealing.

7. 2. The method for producing a grain-oriented electrical steel sheet according to claim 1, wherein the amount of nitriding of the steel sheet after the step of primary recrystallization annealing is 0.02 to 0.04 wt %.

8. a base material containing, by weight percent, 2.5 to 4.0% Si, 0.005% or less (except 0%) C, 0.015 to 0.040% Al, 0.04 to 0.15% Mn, 0.01% or less (except 0%) S, 0.005% or less (except 0%) N, 0.01 to 0.05% Sb, 0.03 to 0.1% Sn, and 0.05 to 0.2% Cr, with the balance being Fe and unavoidable impurities; a metal oxide layer disposed on the substrate; A grain-oriented electrical steel sheet, characterized in that the maximum luminous intensity ratio [I(Ti) / I(Mg)] of the metal oxide layer is 0.05 or more.

9. The grain-oriented electrical steel sheet according to claim 8, wherein the base metal further contains at least one of Ti and V, each of which is 0.002 to 0.01 wt % or a total amount of these elements is 0.002 to 0.01 wt %.

10. The grain-oriented electrical steel sheet according to claim 8 , wherein the base material satisfies the following formula 2: [Formula 2] [Sb]≦[Cr]≦[Sb]+2×[Sn] (In formula 2, [Sb], [Cr] and [Sn] respectively represent the contents (wt%) of Sb, Cr and Sn in the base material.)

11. The grain-oriented electrical steel sheet according to claim 8, wherein the grain-oriented electrical steel sheet has a whiteness of 43 to 51.

12. The grain-oriented electrical steel sheet according to claim 8 , wherein the metal oxide layer contains 0.003 wt % or more of Ti.

13. 9. The grain-oriented electrical steel sheet according to claim 8, further comprising an insulating coating layer located on the metal oxide layer, wherein a ratio of a sum of a thickness of the metal oxide layer and the insulating coating layer to a total thickness of the grain-oriented electrical steel sheet is 0.03 or less.

Citation Information

Patent Citations

  • Production of grain-oriented silicon steel sheet

    JP1995258741A

  • Nitrificating treatment of grain oriented electrical steel sheet having small deviation in longitudinal and width directions and apparatus therefor

    JP1999021627A

  • Primary recrystallization annealed sheet for grain oriented magnetic steel sheet and production method of grain oriented magnetic steel sheet

    JP2015196851A

  • Oriented electrical steel sheet and method therefor

    JP2016145419A

  • Grain-oriented electrical steel sheet and its manufacturing method

    JP2021509149A